Resveratrol dalam Pengobatan Integratif: Menjembatani Pengetahuan Tradisional dan Terapi Modern - Raghda Al-Sayed; Atheel Alwash; Khalid Zainulabdeen; Reem Waleed; Muna Bufaroosha; Shams Ismeal; Nany Hairunisa; Husnun Amalia; Hazim F Abbas; Emad Yousif (Jurnal Biomedika dan Kesehatan, 2026)
Resveratrol is a polyphenolic stilbenoid found in plants such as grapes, berries, and peanuts, widely recognized for its antioxidant, anti-inflammatory, anticancer, antidiabetic, cardioprotective, neuroprotective, and anti-aging properties. Despite extensive preclinical evidence, its clinical translation remains limited by poor bioavailability and inconsistent trial outcomes. This review aims to synthesize current evidence on resveratrol’s mechanisms of action, therapeutic effects across disease models, synergistic drug interactions, and translational challenges, with a focus on its integration into modern integrative medicine. A comprehensive literature search was conducted in PubMed, Scopus, and Web of Science using the terms “resveratrol,” “polyphenol,” “integrative medicine,” and disease-specific keywords. The resuls was Resveratrol demonstrated anticancer effects via apoptosis induction and cell cycle arrest, cardioprotective effects through AMPK/SIRT1/eNOS activation, neuroprotection via Akt/PI3K signaling, and antidiabetic effects through improved insulin sensitivity. Synergistic interactions were identified with metformin (diabetes), statins/aspirin (cardiovascular disease), and chemotherapeutic agents (cancer). Bioavailability and formulation remain major challenges. Conclusion of this study Resveratrol holds significant therapeutic promise in integrative medicine, though robust clinical trials are needed to confirm efficacy and establish safe dosing protocols for clinical application.